2017
DOI: 10.1016/j.jjcc.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impacts of inhibition of renin–angiotensin system in patients with acute ST-segment elevation myocardial infarction who underwent successful late percutaneous coronary intervention

Abstract: In latecomers with STEMI, RAS inhibition improved long-term clinical outcomes after a successful PCI, even in patients with low risk who had relatively preserved LVEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Use of an angiotensin converting enzyme inhibitor or an angiotensin receptor blocker is encouraged in both heart failure and MI patients according to current guidelines because of their beneficial effects against several of the harmful effects of RAAS, including tissue fibrosis, cell apoptosis, cardiac remodeling, fluid and sodium accumulation, and inflammation 6151617. Our group recently reported the beneficial effects of RAAS inhibition on cardiac function, structure, and clinical event-free survival in a large number of latecomer patients with MI in the Korea Acute Myocardial Infarction Registry, whose myocardial salvage and recovery by percutaneous coronary intervention are not expected to be highly effective: RAAS inhibition is even more important in this subset of the population 18. Fimasartan has been proven to have potent antihypertensive effects and already has been used as an AT1 receptor blocker for several years,1920 but its cardioprotective effect for MI or other types of heart failure has not yet clearly been defined.…”
Section: Discussionmentioning
confidence: 99%
“…Use of an angiotensin converting enzyme inhibitor or an angiotensin receptor blocker is encouraged in both heart failure and MI patients according to current guidelines because of their beneficial effects against several of the harmful effects of RAAS, including tissue fibrosis, cell apoptosis, cardiac remodeling, fluid and sodium accumulation, and inflammation 6151617. Our group recently reported the beneficial effects of RAAS inhibition on cardiac function, structure, and clinical event-free survival in a large number of latecomer patients with MI in the Korea Acute Myocardial Infarction Registry, whose myocardial salvage and recovery by percutaneous coronary intervention are not expected to be highly effective: RAAS inhibition is even more important in this subset of the population 18. Fimasartan has been proven to have potent antihypertensive effects and already has been used as an AT1 receptor blocker for several years,1920 but its cardioprotective effect for MI or other types of heart failure has not yet clearly been defined.…”
Section: Discussionmentioning
confidence: 99%
“…-Five studies that identified themselves as RCT and eight other studies that identified themselves as clinical trials [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: : Total Number Of Articles After Applying Inclusion/exclusimentioning
confidence: 99%
“… 45) Use of a renin-angiotensin system inhibitor in STEMI patients undergoing late PCI reduced the 1-year MACE, even in low-risk patients with relatively preserved left ventricular systolic function. 46) …”
Section: Medical Treatmentmentioning
confidence: 99%